The Impact of Advances in Science and Technology on The Moral and Spiritual Intelligence of Student in The Era of Globalization - Yunita, Norma (Indonesian Journal of Islamic Education and Local Culture, 2024)
This article aims to raise awareness about science and technology and its implications for students' moral and spiritual well-being in the era of globalization. It will review the role of science and technology in assisting humans in the process of development and exploration in dealing with complex moral and spiritual issues that are common in the current era of globalization. The rapid development of information and communication makes it easy for individuals to access various facts and perspectives from various sources, which will affect their understanding of morals and spirituality. The data collection technique is observation, namely observing and recording every student's behavior related to the morals and spirituality of Jambi University students in the English Language Education study program. The sample for this study was the R-002 class of 2023, which amounted to 7 people. This research analyzes the various impacts of advances in science and technology on moral and spiritual intelligence in English Language Education students with descriptive methods using a qualitative approach. Keywords: Science and Technology, Moral, Spiritual.